Handbook of GC-MS : fundamentals and applications - Hübschmann, Hans-Joachim (Wiley-VCH, 2025)
"This is the first comprehensive reference work for GC/MS now in its second edition. It offers broad coverage, from sample preparation to the evaluation of MS data, including library searches. Fundamentals, techniques, and applications are described." "A large part of the book is devoted to numerous examples for GC/MS-applications in environmental, food, pharmaceutical and clinical analysis. These proven examples come from the daily practice of various laboratories." "The book also features a glossary of terms and a substance index that helps the reader to find information for his particular analytical problem." "The author presents in a consistent and clear style his experience from numerous user workshops which he has organized. This is a thoroughly revised and updated English edition based on an edition which was highly successful in Germany." --Book Jacket.